Students’ Transportation Problems in University Campus A Case Study, Tripoli University, Libya - Benarafa, Islah; Eryildiz, Demet (The International Journal of Engineering & Information Technology (IJEIT), 2024)
University campuses are small cities in urban areas that are active and attractive destinations. This high level of activity causes severe congestion on campuses and in the surrounding area, especially in urban university locations. Tripoli University campuses are multi-modal and complicated, combining automotive traffic, public transportation, and pedestrians into a single transportation system. This poses a serious problem for university campuses. Vehicular congestion in a campus setting creates several significant conflict areas that range from pedestrian safety to traffic and transit operations. The university has the greatest influence on the surrounding neighborhoods. Innovative transportation approaches can diffuse from higher education to other parts of society. The aim of this study is to understand the main transportation system used at Tripoli University and document a systematic approach to analyze the problems associated with university campus transportation systems and develop solutions to this problem. The research question how can Tripoli University students reach the university campus in less time and more safely? The methodology used in the research will also generate a questionnaire online for students and staff collecting data from other studies and gain knowledge from other countries’ solutions. Effective university campus design has the biggest impact in this area. The expected outcome will be a Based on the findings, this study proposed a mode of transportation that would aid in the discovery of effective solutions to the problem, reduce the amount of time spent traveling every day at the university, and create an integrated university campus.